α-Glucosidase Inhibitors From the Coral-Associated Fungus Aspergillus terreus - Liu, Mengting; Qi, Changxing; Sun, Weiguang; Shen, Ling; Wang, Jianping; Liu, Junjun; Lai, Yongji; Xue, Yongbo; Hu, Zhengxi; Zhang, Yonghui (Frontiers in Chemistry, 2018)
Nine novel butenolide derivatives, including four pairs of enantiomers, named (±)-asperteretones A–D (1a/1b–4a/4b), and a racemate, named asperteretone E (5), were isolated and identified from the coral-associated fungus Aspergillus terreus. All the structures were established based on extensive spectroscopic analyses, including HRESIMS and NMR data. The chiral chromatography analyses allowed the separation of (±)-asperteretones A–D, whose absolute configurations were further confirmed by experimental and calculated electronic circular dichroism (ECD) analysis. Structurally, compounds 2–5 represented the first examples of prenylated γ-butenolides bearing 2-phenyl-3-benzyl-4H-furan-1-one motifs, and their crucial biogenetically related metabolite, compound 1, was uniquely defined by an unexpected cleavage of oxygen bridge between C-1 and C-4. Importantly, (±)-asperteretal D and (4S)-4-decarboxylflavipesolide C were revised to (±)-asperteretones B (2a/2b) and D (4), respectively. Additionally, compounds 1a/1b–4a/4b and 5 were evaluated for the α-glucosidase inhibitory activity, and all these compounds exhibited potent inhibitory potency against α-glucosidase, with IC50 values ranging from 15.7 ± 1.1 to 53.1 ± 1.4 µM, which was much lower than that of the positive control acarbose (IC50 = 154.7 ± 8.1 µM), endowing them as promising leading molecules for the discovery of new α-glucosidase inhibitors for type-2 diabetes mellitus treatment.